Depresión en adolescentes de 14 a 16 años del Colegio 27 de Febrero cd la ciudad de Loja. - Jadán López, Cristina Yasmín (2017)
Depression is a common and serious medical illness; it may be temporary or permanent. Teenagers shows risky behavior, high vulnerability, especially those who hide in crowds with feelings of sadness or self-esteem low. This research was realized in the 27 de Febrero High school which shows us many factors may contribute to the onset of depression in teenagers between 14 and 16 years old. They were applied descriptive cross and qualitative cross-sectional studies as well as the zung test. It was considered the sociodemographic and family conditions of the studied students too; in such a way that it was possible to establish: presence of depression 65.75%. Information that help us to build a depression prevention proposal. Regard to gender, there was a ratio of 1,5 in women, although the sample of men was higher than women. Furthermore, in regards to relationship and/or statistical association between variables of studio a value of p <0.05 (0.047) was found in drug use at the age of 16 years and tobacco consumption p <0.05 (0.031) at the age of 14 years. Teenagers prevention of depression proposal are focused on physical and recreational activities, where the educational community has the biggest challenge of preventing young people from falling into emotional states of sadness, despair, low self-esteem, if the teenagers do not have an special attention , they will not have integral formation. Finally, after have been analyzed the results it was accomplished a brochure where there are some advises for the educational community. Key words: depression, sociodemographic, teenagers, gender.